1984
DOI: 10.2134/jeq1984.00472425001300040012x
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Assessment Model for Trace Organics in Soil: II. Chemical Classification and Parameter Sensitivity

Abstract: In this paper, the organic chemical transport screening model developed in Jury et al. (1983) is simplified by dividing chemicals into volatilization and mobility categories. The volatilization classification is based on whether or not the predominant resistance to volatilization loss lies in the soil or in the boundary layer above the soil surface. This categorization reduces to a condition on the Henry's constant (KH) and organic C partition coefficient (Koc) when standard values are used to represent soil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0
2

Year Published

1986
1986
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(73 citation statements)
references
References 0 publications
2
69
0
2
Order By: Relevance
“…Laboratory research established that the rate of volatilization from soil is controlled by rate of movement of the organic chemical to the soil surface by mass flow in water and by diffusion . The output from a pesticide screening model (Jury et al, 1984a) indicated that rate of movement to the soil surface relative to movement of the pesticide through the stagnant air boundary ,layer above the surface can also control volatilization and accumulation at the soil surface.Volatilization rate from a surface deposit depends only on the rate of movement of the chemical away from the evaporating surface and its vapor pressure. In contrast, .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Laboratory research established that the rate of volatilization from soil is controlled by rate of movement of the organic chemical to the soil surface by mass flow in water and by diffusion . The output from a pesticide screening model (Jury et al, 1984a) indicated that rate of movement to the soil surface relative to movement of the pesticide through the stagnant air boundary ,layer above the surface can also control volatilization and accumulation at the soil surface.Volatilization rate from a surface deposit depends only on the rate of movement of the chemical away from the evaporating surface and its vapor pressure. In contrast, .…”
mentioning
confidence: 99%
“…Models developed for estimating volatilization rates are based on equations describing the rate of movement of the chemical to the surface by diffusion and/or by convection, and away from the surface through the air boundary layer by diffusion Mayer et al, 1974;Jury et al, 1980Jury et al, , 1983. Additionally, the proportion of the chemical in soil that will be lost by volatilization depends on the resistance of the chemical to degradation.In a series of papers, Jury et al (1983Jury et al ( , 1984a, b, c) described and applied a model for assessing relative volatility, mobility, and persistance of pesticides and other trace organics in soil. The model allows the organica to be present in the soil in the adsorbed, solution, and …”
mentioning
confidence: 99%
“…The first model used was the Behavior Assessment Model for Trace Organics in Soil (Jury et al, 1983(Jury et al, , 1984a(Jury et al, , 1984b(Jury et al, , 1984c(Jury et al, , and 1991. Application of the phase partitioning components of this model showed that the mass fractions of TNT and DNT in soils were predominantly sorbed to the soil particles (90+%), the majority of the remaining mass is dissolved in the soil pore water (10+%), and only a trace is found in the soil gas (~ 10 -6 %).…”
Section: Analytical Model Analysis To Show Critical Propertiesmentioning
confidence: 99%
“…Digital computer models to evaluate pesticide fate and transport in agricultural soils have been developed by numerous researchers, including Jury and others (1983;1984a;1984b;1984c;, Rutledge and Helgesen (1989), Mackay (1991), and Mackay and Stiver (1991). Rao and others (1985) compared ranks of pesticide leaching potentials produced by six simple models.…”
Section: Previous Investigationsmentioning
confidence: 99%